Mathematical model of a counter-flow rotary dryer for automation control a case study in a granulated organic fertilizer drying process in a chicken farm - Sringak, Chayaphan; Suntivarakorn, Ratchaphon; Radpukdee, Thana (Engineering and Applied Science Research, 2013)
In this paper presents a mathematical model of a granulated organic fertilizer drying process. The process dryingis operated by a courter-flow rotary dryer. The governing equation was analyzed by relationship between energyand mass balance of wet solid and gas inside a virtual control volume. The virtual volume was combined in series.The out puts of each one will be the input of the next volume. This discrete volume method was used to reduce theeffect of changing the parameters due to the length of the rotary dryer. The rotary dryer consists of a burner thatgenerates hot gas supplying to the dryer and the rotary kiln used to reduce the moisture out of the wet solid.Its controlled variables are mass flow rate of wet solid and fuel flow rate of methane. While responses are amount of moisture in the wet solid and hot gas temperature out of the end of the rotary kiln dryer. The model of the rotarydryer can be used to design a control law based on the variable structure control for multi input-output system. Keywords: Biogas, Variable structure control